Colorimeter Portable to Determine Ammonium Using to Manure Tetector - Yohan Yohan; Fifit Astuti; Adimas Wicaksana (Piston: Journal of Technical Engineering, 2021)
Contruction of colorimeter and calibrationare presented in this paper. In this investigation involves design, detection system, and measurement.Colorimeter was fabricated in dimension (10 x 10 x 6)cm3 consist of light source, modular data, and transducer. The light sources were LEDs which responds of  wavelength peak at 467 nm on 0,141 W/m2. Arduino Uno R3 is used to data tabulation in calculate absorbance system with 1.8.5 sofware. Then transducer was used a LDR which useful for consider the light in sample and reference. The calibration curve of ammonium consentration shows  linierity range at 0.1 to 2 ppm with y = 0.0234x + 0.0905, R= 0.9716. The portable colorimeter was found accuration and precision about 88,7 % and 99,8%. the portabel colorimeter gives the best result in this investigation and use to fake manure detector in Agricultural application for domestic farmer.